RISK ANALYSIS OF IMPACT INVESTMENT DURING THE POST-CONFLICT RECOVERY OF UKRAINE'S ECONOMY - Artemenko, Alina; Plastun, Alex; Mykhailov, D. (Socio-economic relations in the digital society, 2022)
This study is devoted to examining the concept of the impact of investment strategy implementation during the post-conflict (post-war) period with the aim of economic recovery in Ukraine. The main focus is on the analyzing approaches to assess the investment attractiveness of war-affected regions, as they are politically unstable, with weak civil infrastructure, a dysfunctional legal system, and a polarized society. Taken together, all these create a high risk to investors. The experience of such leading international organizations as the United Nations (UN), the OECD, the World Bank, and the International Finance Corporation (IFC) in their work on developing methods of investment risk assessing and identifying priority areas for investment is reviewed. Practical cases of successful implementation of impact investment strategies in West Africa are presented. Particular attention is paid to studying the prospects of impact investment in Ukraine during the military conflict and macroeconomic instability based on the analysis of key country's problems as a result of the war. It is determined that the general profiling of the region is the primary element of taking investment decision as it allows to specify the territorial boundaries of the investment project, identify economic problems in the region, employment, etc. However, any final investment decision must be taken after the end of the conflict. As a result of empirical research, a generalized matrix of SWOT analysis is formed to assess the risk level of the impact investment project in the post-conflict region; developed an indicators typology of investment risk assessment and economic profiling of the region, which could potentially be the object of impact investment.
Keywords: investment project; investment risk; impact investments; military conflict; macroeconomic instability